Pembuatan Nomor Induk Berusaha (NIB) Melalui Online Single Submission - Ika Wulandari; Martinus Budiantara (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Currently, governments offer a lot of assistance, some of those are assisting and training to UMK as of the Covid 19 pandemi impact. To obtain these facilities, UMK is required to have a Business Identification Number (NIB). This activity is carried out to answer the problems, and aims to introduce and improve the understanding of making NIB and IUMK. This activity was carried out in June 2021 for 11 UMK in Balecatur, Gamping. The method used was sosialization, training and mentoring. The implementation was including the delivery of theory and practice of business legalities making. The training result was the participants' understanding about OSS, NIB and IUMK increased. It could be seen from the average pre-test and post-test scores rose from 33 to 82. Now the number of participants who had business legality increased from 18% to 100%. By having NIB and IUMK, participants will get convenience in various things, such as financing, assisting and training from related parties.